Lipin1 Is a Key Factor for the Maturation and Maintenance of Adipocytes in the Regulatory Network with CCAAT/Enhancer-binding Protein α and Peroxisome Proliferator-activated Receptor γ2 - Yookyung Koh; Min Young Lee; Jae Woo Kim; Minji Kim; Jong‐Seok Moon; Yoo-Jung Lee; Yong‐Ho Ahn; Kyung‐Sup Kim (2008)
Lipin1 expression was induced at a late stage of differentiation of 3T3-L1 preadipocytes and maintained at high levels in mature adipocytes. Knockdown of expression of lipin1 by small interfering RNA in 3T3-L1 preadipocytes almost completely inhibited differentiation into adipocytes, whereas overexpression of lipin1 accelerated adipocyte differentiation, demonstrating that lipin1 is required for adipocyte differentiation. In mature adipocytes, transfection of lipin1-small interfering RNA decreased the expression of adipocyte functional genes, indicating the involvement of lipin1 in the maintenance of adipocyte function. Lipin1 increases the transcription-activating function of peroxisome proliferator-activated receptor γ2 (PPARγ2) via direct physical interaction, whereas lipin1 did not affect the function of other adipocyte-related transcription factors such as C/EBPα, liver X-activated receptor α, or sterol regulatory element binding protein 1c. In mature adipocytes, lipin1 was specifically recruited to the PPARγ-response elements of the phosphoenolpyruvate carboxykinase gene, an adipocyte-specific gene. C/EBPα up-regulates lipin1 transcription by directly binding to the lipin1 promoter. Based on the existence of a positive feedback loop between C/EBPα and PPARγ2, we propose that lipin1 functions as an amplifier of the network between these factors, resulting in the maintenance of high levels of the specific gene expression that are required for adipogenesis and mature adipocyte functions. Lipin1 expression was induced at a late stage of differentiation of 3T3-L1 preadipocytes and maintained at high levels in mature adipocytes. Knockdown of expression of lipin1 by small interfering RNA in 3T3-L1 preadipocytes almost completely inhibited differentiation into adipocytes, whereas overexpression of lipin1 accelerated adipocyte differentiation, demonstrating that lipin1 is required for adipocyte differentiation. In mature adipocytes, transfection of lipin1-small interfering RNA decreased the expression of adipocyte functional genes, indicating the involvement of lipin1 in the maintenance of adipocyte function. Lipin1 increases the transcription-activating function of peroxisome proliferator-activated receptor γ2 (PPARγ2) via direct physical interaction, whereas lipin1 did not affect the function of other adipocyte-related transcription factors such as C/EBPα, liver X-activated receptor α, or sterol regulatory element binding protein 1c. In mature adipocytes, lipin1 was specifically recruited to the PPARγ-response elements of the phosphoenolpyruvate carboxykinase gene, an adipocyte-specific gene. C/EBPα up-regulates lipin1 transcription by directly binding to the lipin1 promoter. Based on the existence of a positive feedback loop between C/EBPα and PPARγ2, we propose that lipin1 functions as an amplifier of the network between these factors, resulting in the maintenance of high levels of the specific gene expression that are required for adipogenesis and mature adipocyte functions. Adipose tissue plays an essential role in maintaining metabolic homeostasis (1.Spiegelman B.M. Flier J.S. Cell. 1996; 87: 377-389Abstract Full Text Full Text PDF PubMed Scopus (1156) Google Scholar). White adipose tissue takes up fatty acids derived from the diet or the liver as well as increases the uptake of glucose in response to insulin by recruiting glucose transporter 4 (GLUT4) 2The abbreviations used are: GLUT4, glucose transporter 4; DMEM, Dulbecco's modified Eagle's medium; HA, hemagglutinin; nt, nucleotide(s); PPAR, peroxisome proliferator-activated receptor; PPRE, PPARγ response element; C/EBP, CCAAT/enhancer-binding proteins β and δ; LXR, liver X-activated receptor α; SREBP-1c, sterol regulatory element binding protein 1c; siRNA, small interfering RNA; ChIP, chromatin immunoprecipitation; PEPCK, phosphoenolpyruvate carboxykinase; aP2, acid-binding protein.2The abbreviations used are: GLUT4, glucose transporter 4; DMEM, Dulbecco's modified Eagle's medium; HA, hemagglutinin; nt, nucleotide(s); PPAR, peroxisome proliferator-activated receptor; PPRE, PPARγ response element; C/EBP, CCAAT/enhancer-binding proteins β and δ; LXR, liver X-activated receptor α; SREBP-1c, sterol regulatory element binding protein 1c; siRNA, small interfering RNA; ChIP, chromatin immunoprecipitation; PEPCK, phosphoenolpyruvate carboxykinase; aP2, acid-binding protein. to the plasma membrane. Then white adipose tissue stores the glucose or fatty acids as a form of triacylglyceride and releases free fatty acids during states of starvation. Recent studies have shown that adipose tissue secretes various humoral factors called adipocytokines which play numerous functions associated with food intake, insulin sensitivity, energy homeostasis, inflammatory responses, and atherogenesis (2.Flier J.S. Cell. 2004; 116: 337-350Abstract Full Text Full Text PDF PubMed Scopus (952) Google Scholar). In obese subjects adipocytes cannot function adequately, thereby causing various metabolic syndromes including insulin resistance, dyslipidemia, and coronary-vascular disease (3.Scott C.L. Am. J. Cardiol. 2003; 92: 35-42Abstract Full Text Full Text PDF PubMed Scopus (159) Google Scholar, 4.Must A. Spadano J. Coakley E.H. Field A.E. Colditz G. Dietz W.H. J. Am. Med. Assoc. 1999; 282: 1523-1529Crossref PubMed Scopus (3589) Google Scholar, 5.Kress A.M. Hartzel M.C. Peterson M.R. Prev. Med. 2005; 41: 63-69Crossref PubMed Scopus (49) Google Scholar, 6.Nowicki E.M. Billington C.J. Levine A.S. Hoover H. Must A. Naumova E. Mil. Med. 2003; 168: 252-256Crossref PubMed Scopus (29) Google Scholar). Lipodystrophy leads to the same condition as obesity due to lack of adipocyte function (7.Schott M. Scherbaum W.A. Bornstein S.R. N. Engl. J. Med. 2004; 351: 103-104Crossref PubMed Scopus (11) Google Scholar, 8.Reitman M.L. Arioglu E. Gavrilova O. Taylor S.I. Trends Endocrinol. Metab. 2000; 11: 410-416Abstract Full Text Full Text PDF PubMed Scopus (170) Google Scholar, 9.Hegele R.A. Trends Endocrinol. Metab. 2003; 14: 371-377Abstract Full Text Full Text PDF PubMed Scopus (74) Google Scholar). Thus, studying the molecular mechanisms that control adipose tissue development and function is important for understanding the pathophysiology of metabolic syndromes. Adipogenesis is a process in which premature cells acquire adipocyte-specific functions. A complex network of transcription factors is developed during this process in response to extracellular adipogenic stimuli. In 3T3-L1 preadipocyte cells the CCAAT/enhancer-binding proteins β and δ (C/EBPβ and C/EBPδ) are induced immediately upon adipogenic hormonal stimuli, and they are expressed for approximately 2 days after which C/EBPα and peroxisome proliferator-activated receptor γ2 (PPARγ2) are induced (10.Christy R.J. Kaestner K.H. Geiman D.E. Lane M.D. Proc. Natl. Acad. Sci. U. S. A. 1991; 88: 2593-2597Crossref PubMed Scopus (329) Google Scholar, 11.Clarke S.L. Robinson C.E. Gimble J.M. Biochem. Biophys. Res. Commun. 1997; 240: 99-103Crossref PubMed Scopus (187) Google Scholar). Expression of C/EBPα and PPARγ2 is induced by C/EBPβ and C/EBPδ during the early stage of adipogenesis. During the late stages of adipogenesis when the expression of C/EBPβ and C/EBPδ has diminished, expression of C/EBPα and PPARγ2 is induced by each other, thereby keeping these proteins at high levels in mature adipocytes (12.Ramji D.P. Foka P. Biochem. J. 2002; 365: 561-575Crossref PubMed Google Scholar). C/EBPα and PPARγ2 activate the expression of genes important for adipocyte function, thereby maturing adipocytes and maintaining adipocyte-specific functions (13.Farmer S.R. Cell Metab. 2006; 4: 263-273Abstract Full Text Full Text PDF PubMed Scopus (1364) Google Scholar). Liver X-activated receptor α (LXRα) stimulates the expression of PPARγ2 by directly binding to the promoter region as well as up-regulating sterol regulatory element binding protein 1c (SREBP-1c), which induces PPARγ2 expression. Because PPARγ2 can up-regulate LXRα expression, the positive network between PPARγ2, LXRα, and SREBP-1c is also considered to be important during adipogenesis (14.Seo J.B. Moon H.M. Kim W.S. Lee Y.S. Jeong H.W. Yoo E.J. Ham J. Kang H. Park M.G. Steffensen K.R. Stulnig T.M. Gustafsson J.A. Park S.D. Kim J.B. Mol. Cell. Biol. 2004; 24: 3430-3444Crossref PubMed Scopus (206) Google Scholar). Lipin1 was discovered as a mutated gene in a fatty liver dystrophic (fld) mouse using a positional cloning approach (15.Peterfy M. Phan J. Xu P. Reue K. Nat. Genet. 2001; 27: 121-124Crossref PubMed Scopus (467) Google Scholar). A null mutation in the lipin1 gene in these mice leads to lipodystrophy characterized by a severely reduced mass of adipose tissue and a deficiency in adipocyte differentiation (16.Reue K. Peterfy M. Curr. Atheroscler. Rep. 2000; 2: 390-396Crossref PubMed Scopus (29) Google Scholar, 17.Reue K. Xu P. Wang X.P. Slavin B.G. J. Lipid Res. 2000; 41: 1067-1076Abstract Full Text Full Text PDF PubMed Google Scholar). Lack of adipose tissue in fld mice results in insulin resistance (16.Reue K. Peterfy M. Curr. Atheroscler. Rep. 2000; 2: 390-396Crossref PubMed Scopus (29) Google Scholar, 17.Reue K. Xu P. Wang X.P. Slavin B.G. J. Lipid Res. 2000; 41: 1067-1076Abstract Full Text Full Text PDF PubMed Google Scholar) and circulating hyperlipidemia (18.Langner C.A. Birkenmeier E.H. Ben-Zeev O. Schotz M.C. Sweet H.O. Davisson M.T. Gordon J.I. J. Biol. Chem. 1989; 264: 7994-8003Abstract Full Text PDF PubMed Google Scholar). In previous reports lipin1 was found to be expressed at a high level in adipose tissue (15.Peterfy M. Phan J. Xu P. Reue K. Nat. Genet. 2001; 27: 121-124Crossref PubMed Scopus (467) Google Scholar), and the expression level of lipin1 was positively correlated with insulin sensitivity, which is associated with adipocyte function (19.van Harmelen V. Ryden M. Sjolin E. Hoffstedt J. J. Lipid Res. 2007; 48: 201-206Abstract Full Text Full Text PDF PubMed Scopus (67) Google Scholar). These facts suggest that lipin1 plays an important role in adipogenesis and in the function of mature adipocytes. However, the molecular function and regulation of lipin1 remains unclear. Recently, the yeast homolog of lipin1 was reported to have phosphatidic acid phosphohydrolase enzymatic activity (20.Han G.S. Wu W.I. Carman G.M. J. Biol. Chem. 2006; 281: 9210-9218Abstract Full Text Full Text PDF PubMed Scopus (421) Google Scholar, 21.Scavello Jr., G.S. Paluru P.C. Zhou J. White P.S. Rappaport E.F. Young T.L. Mol. Vis. 2005; 11: 97-110PubMed Google Scholar). Phosphatidic acid phosphohydrolase creates diacylglycerol from phosphatidic acid, which is the rate-limiting step in triacylglycerol synthesis. A defect in triacylglycerol synthesis is known to block adipocyte differentiation (22.Gale S.E. Frolov A. Han X. Bickel P.E. Cao L. Bowcock A. Schaffer J.E. Ory D.S. J. Biol. Chem. 2006; 281: 11082-11089Abstract Full Text Full Text PDF PubMed Scopus (104) Google Scholar). Therefore, the phosphatidic acid phosphohydrolase activity of lipin1 relates to the molecular function of lipin1 in adipogenesis. However, there are several lines of evidence that suggest the possibility of a nuclear function for lipin1 as well. Two domains of lipin1 are highly conserved among species, the N-terminal conserved domain (NLIP) and the C-terminal conserved domain (CLIP). NLIP domain is known to interact with several nuclear proteins (23.Tange Y. Hirata A. Niwa O. J. Cell Sci. 2002; 115: 4375-4385Crossref PubMed Scopus (80) Google Scholar). Although lipin1 lacks a DNA binding domain, a yeast homolog of lipin1 was found in the promoter regions of genes involved in phospholipid biosynthesis (24.Santos-Rosa H. Leung J. Grimsey N. Peak-Chew S. Siniossoglou S. EMBO J. 2005; 24: 1931-1941Crossref PubMed Scopus (288) Google Scholar), suggesting that lipin1 could be involved in the regulation of gene transcription by interacting with transcription factors. Furthermore, recent studies found that lipin1 acts as an amplifier of PPARα action by increasing the interaction between peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) and PPARα in liver (25.Finck B.N. Gropler M.C. Chen Z. Leone T.C. Croce M.A. Harris T.E. Lawrence Jr., J.C. Kelly D.P. Cell Metab. 2006; 4: 199-210Abstract Full Text Full Text PDF PubMed Scopus (429) Google Scholar). In this study we investigated the expression of lipin1 and examined its potential role in adipogenesis. We also found that lipin1 increases the transcription-activating function of PPARγ2 via direct a physical interaction and is up-regulated at the transcriptional level by C/EBPα. These results provide compelling evidence that lipin1 reinforces the positive feedback loop between C/EBPα and PPARγ2, which is essential for adipogenesis and the maintenance of adipocyte functions. Cell Culture, in Vitro Differentiation—3T3-L1 and NIH3T3 cells were obtained from American Type Culture Collection. 3T3-L1 preadipocytes were propagated and maintained in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% calf serum. For in vitro differentiation, 2-days post-confluent (designated day 0) cells were treated with DMEM containing 10% fetal bovine serum, 520 μm 3-isobutyl-1-methylzanthine, 1 μm dexamethasone, and 167 nm insulin until day 2. The medium was then replaced and incubated with DMEM supplemented with 10% fetal bovine serum and 167 nm insulin until day 4. The medium was then replaced with DMEM supplemented with 10% fetal bovine serum, which was renewed daily until day 8. NIH3T3 cells were propagated and maintained in DMEM supplemented with 10% fetal bovine serum. Western Blot Analysis—Cultured cells for Western blot analysis were washed once with cold phosphate-buffered saline and then harvested with whole cell lysis buffer (1% SDS, 60 mm Tris-HCl, pH 6.8), heated at 100 °C for 10 min, and centrifuged at 12,000 rpm for 5 min at room temperature. Supernatants were transferred to new tubes and used for Western blot analysis. Plasmid Constructs, Transfections, and Luciferase Assays—To generate the lipin1β-V5 expression vector, full-length lipin1β (accession number BC018071) cDNA was amplified by PCR using the primers 5′-CACCATGAATTACGTGGGGCAGTTA-3′ and 5′-CGCTGAGGCAGAATGAATGTCCTG-3′ and cloned into the pcDNA3.1-V5/His-TOPO expression vector (Invitrogen) and pSG5-FLAG-tagged expression vector, resulting in pcDNA-lipin1β-V5 and pSG5-FLAG-lipin1β. The pSG5-FLAG-lipin1β (1–441) was generated by self-ligation after the removal of BamHI fragment from pSG5-FLAG-lipin1β. The pSG5-FLAG-lipin1-(425–926) were produced by cloning lipin1 cDNA fragment amplified using primers 5′-ACGAAGCCGACATCTTGGTGCT-3′ and 5′-CGCTGAGGCAGAATGAATGTCCTG-3′ into pSG5-FLAG-tagged expression vector. The expression plasmids pCMV-rC/EBPα and pCMV-rC/EBPβ were gifts from Dr. J. R. Cardinaux (Centre de Neurosciences Psychiatriques, Lausanne, Switzerland). The expression plasmids pCMX-mPPARγ, pCMX-mRXRα, pCMX-mLXRα, and 3xLXRE-tk-LUC were gifts from Dr. D. Mangelsdorf (26.Peet D.J. Janowski B.A. Mangelsdorf D.J. Curr. Opin. Genet. Dev. 1998; 8: 571-575Crossref PubMed Scopus (321) Google Scholar). The pSG5-HA-PPARγ, pSG5-HA-PPARγ-(1–273), and pSG5-HA-PPARγ-(274–475) were generated from pCMX-mPPARγ by cloning respective mPPARγ cDNA into pSG5-HA-tagged expression vector. The expression plasmid pCMV7-hSREBP-1c was previously described (27.Kim H.I. Kim J.W. Kim S.H. Cha J.Y. Kim K.S. Ahn Y.H. Diabetes. 2000; 49: 1517-1524Crossref PubMed Scopus (105) Google Scholar). The 3xPPRE-tk-LUC plasmid, which contains three copies of the PPARγ-response element and a luciferase reporter gene, was received from Jae-Bum Kim (14.Seo J.B. Moon H.M. Kim W.S. Lee Y.S. Jeong H.W. Yoo E.J. Ham J. Kang H. Park M.G. Steffensen K.R. Stulnig T.M. Gustafsson J.A. Park S.D. Kim J.B. Mol. Cell. Biol. 2004; 24: 3430-3444Crossref PubMed Scopus (206) Google Scholar). The human FAS promoter-luciferase reporter plasmid containing the sequences from -2.7 to +1.8 kilobases of the FANS gene, was previously described (28.Lee, M. Y., Moon, J. S., Park, S. W., Koh, Y. K., Ahn, Y. H., and Kim, K. S. (2008) Biochem. J., in pressGoogle Scholar). The human G6Pase promoter-luciferase reporter plasmid, human glucose-6-phosphatase (-1227/+57), which contains a 1.2-kilobase-proximal promoter fragment extending from nt -1227 to +57, was a gift from Dr. D. Schmoll (29.Schmoll D. Walker K.S. Alessi D.R. Grempler R. Burchell A. Guo S. Walther R. Unterman T.G. J. Biol. Chem. 2000; 275: 36324-36333Abstract Full Text Full Text PDF PubMed Scopus (293) Google Scholar). The human lipin1 promoter-luciferase reporter plasmid, pGL3BA-hLipin1, was constructed by generating a lipin1 gene fragment extending from nt -1300 to +524 via PCR using the primers 5′-TCAGCAGTTTTGGGCAGCCGTGAT-3′ and 5′-AACTGCAGCGCTGGAATCCTAACT-3′ and then cloning the fragment into the pGL3-basic-acceptor luciferase vector. The pGL3-basic-acceptor luciferase was generated by inserting the splicing acceptor sequence consisting of 163 bp to the 3′ end of the first intron and 19 bp to the 5′ end of the 2nd exon of rat ACLY gene at HindIII site of pGL3-Basic. The pRL-SV40 construct, which was the expression vector of renilla luciferase, was obtained from Promega Corp. (Madison, WI). For transfection of NIH3T3, cells were plated in 10-cm plates or 6-well plates 1 day before transfection. When the cells reached 60–80% confluency, they were transiently transfected with plasmids using Lipofectamine PLUS™ (Invitrogen) following the supplier's protocol. For transfection of 3T3-L1, cells were plated at 8 × 105 cells/60-mm dish or 3 × 105 cells per 30-mm dish 1 day before transfection. When the cells reached 90–95% confluency, they were transiently transfected with plasmids using FuGENE® HD Transfection Reagent (Roche Applied Science) following the supplier's protocol. Luciferase activities in whole cell lysates were measured using a Dual-Luciferase® reporter assay system (Promega). The luciferase activity was normalized to the level of renilla luciferase activities of each cell lysate using a pRL-SV40 construct. Small Interfering RNA (siRNA)—siRNA oligonucleotides specific for regions in the lipin1 mRNA were constructed according to the manufacturer's protocol for the Silencer® siRNA construction kit (Ambion, Austin, TX). Several siRNA oligonucleotides were screened and tested for their ability to silence lipin1 expression. The most active of these oligonucleotides for lipin1 (sense, 5′-GGAACUCUGUAGACAGAAUtt-3′; antisense, 5′-AUUCUGUCUACAGAGUUCCtc-3′) effectively blocked the expression of lipin1. Negative control #1 siRNA (Ambion) was used as a control. For transfection, 3T3-L1 preadipocytes were plated at 8 × 105 cells per 60-mm dish 1 day before transfection. Fifty nanomolar double-stranded 21-mer siRNA was transfected into 3T3-L1 cells using 15 μl of RNAiMAX (Invitrogen) according to the manufacturer's protocol. Confluency of the cells at the time of transfection was ∼90–95%. The cells were incubated in medium containing the siRNA-RNAiMAX complex for 6 h. The medium was then replaced with DMEM supplemented with 10% calf serum, and the cells were incubated for additional 12 h until they were just confluent. The medium was then replaced with that containing the conventional hormonal stimuli. Reverse Transcription and Real-time PCR—Total RNA was purified from cultured cells with TRIzol® reagent according to the manufacturer's instructions (Invitrogen). First-strand cDNA synthesis was performed using oligo dT-primers with SuperScript™ II reverse transcriptase (Invitrogen) following the supplier's protocol. Quantitative real-time PCR analyses were performed on the 7300 Real Time PCR System (Applied Biosystems, Foster City, CA) using SYBR® Green PCR Master Mix (Applied Biosystems). Each assay was performed in triplicate and included four serial dilution points of a control cDNA, a no-template control, and each sample cDNA. The relative concentrations of the genes of interest, and the endogenous control (actin) were calculated by plotting the threshold cycle (Ct) versus the log of the serial dilution points. The relative expression of the gene of interest was determined after normalizing to the endogenous control. The sequences of primers used for real-time PCR can be found in Table 1.TABLE 1Oligonucleotides used in PCR and ChIP assayNameSequenceMouse lipin1 sense5′-CGA TGG ATG GAA GCA GAA CTC-3′Mouse lipin1 antisense α5′-AGC CTG AAG GAC TGG GGC TGG-3′Mouse lipin1 antisense β5′-AAG ACT GCA GAG GAC AAG AGC-3′Mouse lipin1 antisense Total5′-TGG GAT ACG ATG CTG ACT-3′Mouse C/EBPβ sense5′-CAA GCT GAG CGA CGA GTA CA-3′Mouse C/EBPβ antisense5′-CAG CTG CTC CAC CTT CTT CT-3′Mouse PPARγ2 sense5′-CCA GAG CAT GGT GCC TTC GCT-3′Mouse PPARγ2 antisense5′-CAG CAA CCA TTG GGT CAG CTC-3′Mouse C/EBPα sense5′-GAA CAG CAA CGA GTA CCG GGT A-3′Mouse C/EBPα antisense5′-GCC ATG GCC TTG ACC AAG GAG-3′Mouse aP2 sense5′-GAA CCT GGA AGC TTG TCT TCG-3′Mouse aP2 antisense5′-ACC AGC TTG TCA CCA TCT CG-3′Mouse PEPCK sense5′-TCA TCA TCA CCC AAG AGC AGA G-3′Mouse PEPCK antisense5′-CTT TCA TGC ACC CTG GGA AC-3′Mouse GLUT4 sense5′-TCG TCA TTG GCA TTC TGG TTG-3′Mouse GLUT4 antisense5′-AGC TCG TTC TAC TAA GAG CAC G-3′Mouse SREBP-1c sense5′-GGA GCC ATG GAT TGC ACA TT-3′Mouse SREBP-1c antisense5′-CTG AGT GTT TCC TGG AAG G-3′Mouse LXRα sense5′-GAG AAG CTG GTG GCT GCC CA-3′Mouse LXRα antisense5′-AGC TGT AGG AAG CCA GGG AG-3′Mouse β-actin sense5′-TTG TAA CCA ACT GGG ACG ATA TGG-3′Mouse β-actin antisense5′-CGA CCA GAG GCA TAC AGG GAC AAC-3′PEPCK (–1096/–665) sense5′-TCTGAACTCCGACAAGCAAGCTCT-3′PEPCK (–1096/–665) antisense5′-ACGTACATACTGACCCCTGCTCT-3′PEPCK (–665/–375) sense5′-AGAGCAGGGGTCAGTATGTACGTA-3′PEPCK (–665/–375) antisense5′-TGGACTTCATATGTTGCTGGCTGC-3′PEPCK (–2998/–2722) sense5′-GCCTCTCTCTCTATATATATAAAT–3′PEPCK (–2998/–2722) antisense5′-ATCTATCTATCTATCTACCCATCT-3′PPARγ2 (–537/–375) sense5′-TATCTGGTGTTTCATAACTTAGAGATTAAG-3′PPARγ2 (–537/–375) antisense5′-ATTACAAGGAAAACGTTGCTACATTGTCTC-3′SREBP–1c (–410/–170) antisense5′-GAACCAGCGGTGGGAACACAGAGC-3′SREBP–1c (–410/–170) asense5′-GACGGCGGCAGCTCGGGTTTCTC-3′FAS (–227/–50) sense5′-GACGGAAGCAGGCGGGGGCT-3′ Open table in a new tab Oil Red O Staining—Cultured cells for Oil Red O staining were washed once with phosphate-buffered saline then fixed with 3.7% formaldehyde for 2 min at room temperature. After 1 wash with water, cells were added to the Oil Red O working solution (0.5% Oil Red O in isopropanol:water, ratio 3:2) and incubated for 1 h at room temperature. The Oil Red O solution was then aspirated, and stained cells were washed with water and then observed. Coimmunoprecipitation Assay—For coimmunoprecipitation assays, PPARγ and lipin1 were overexpressed in NIH3T3 cells as indicated in Fig. 6. Transfected cells were incubated for 2 days, then washed twice with phosphate-buffered saline, scraped off, and centrifuged at 5000 rpm for 2 min at 4 °C. Pellets were lysed in lysis buffer (50 mm Tris, pH 7.4, 150 mm NaCl, 0.2% Triton X-100, 0.3% Nonidet P-40) and centrifuged at 13,000 rpm for 10 min at 4 °C. Supernatants were transferred to a new tube after which 1-ml aliquots were rotated with 20 μl of protein A/G plus-agarose (Santa Cruz Biotechnology, Inc., Santa Cruz, CA) for 10 min at 4 °C and centrifuged at 3000 rpm for 3 min at 4 °C. Supernatants were transferred to a new tube and incubated with rotation for 12 h at 4 °C with anti-V5 or anti-HA antibody (Santa Cruz Biotechnology). The lysates were then added to 20 μl of protein A/G plus-agarose (Santa Cruz Biotechnology) and rotated for 90 min at 4 °C. After centrifugation at 3000 rpm for 3 min at 4 °C, the pellets were resuspended in wash buffer (lysis buffer:phosphate-buffered saline, 1:2) then incubated with rotation for 10 min at 4 °C. This wash step was repeated three times, and then the immunoprecipitants were heated with SDS-containing sample buffer at 95 °C for 5 min after which Western blotting was performed using either an anti-PPARγ antibody or an anti-FLAG antibody (Sigma-Aldrich). Chromatin Immunoprecipitation (ChIP) Assay—To confirm lipin1 recruitment into the promoter region on which PPARγ or other factors bind, a ChIP assay was carried out using a rabbit polyclonal anti-lipin1 antibody (Millipore, Billerica, MA) and ChIP assay kit (Millipore) following the supplier's protocol with in vitro differentiated 3T3-L1 mature adipocytes (day 8) and 3T3-L1 preadipocytes (day 0). 3T3-L1 cells cultured in 6-cm dishes were treated with formaldehyde at the indicated time points. The cross-linked adducts were resuspended and sonicated, resulting in DNA fragments of 200 to 1000 bp. Then the fragmented chromatin samples were immunoprecipitated with anti-lipin1 antibody. Immunoprecipitated chromatin samples were reverse-cross-linked and purified and then analyzed by PCR. DNA prepared from chromatin samples served as a positive control (input). DNA prepared from chromatin samples immunoprecipitated without antibody served as a negative control. The sequences of the PCR primers can be found in Table 1. Electrophoretic Mobility Shift Assay—To confirm the binding of C/EBPα to the putative C/EBPα-binding sequence in the lipin1 promoter, a gel retardation assay was performed. The oligonucleotide encoding the putative C/EBPα-binding site in the lipin1 promoter was used as probe. Wild-type and mutant oligonucleotides were used as competitors. The sequence of the wild-type oligonucleotide probe was (-647) 5′-ATAACGTCTGGTGGTGAAATGATTTCCATCAA-3′ (-678), and the sequence of the mutant oligonucleotide probe was (-647) 5′-ATAACGTCTGGTGGTAACCAGATTTCCATCAA-3′ (-678), where the italicized bases indicate the putative C/EBPα-binding site, and the underlined bases are mutated. The 32P-labeled probe was incubated with 5 μg of either cell extract from NIH3T3 cells that overexpressed C/EBPα or from cells that had been transfected with the empty vector. After loading the reaction mixtures onto a PAGE gel, the bands were examined and compared. Lipin1 Is Induced in the Late Stages of Adipocyte Differentiation—To determine the function of lipin1 in white adipose tissue, lipin1 expression was examined during adipocyte differentiation of 3T3-L1 preadipocytes, which is a well characterized differentiation model after exposure of the cells to adipogenic hormonal stimuli (30.Ntambi J.M. Buhrow S.A. Kaestner K.H. Christy R.J. Sibley E. Kelly Jr., T.J. Lane M.D. J. Biol. Chem. 1988; 263: 17291-17300Abstract Full Text PDF PubMed Google Scholar). During adipocyte differentiation, expression of lipin1 mRNA began to increase 2 days after induction of differentiation and was continuously elevated further, thereby reaching a maximum level in mature adipocytes (Fig. 1A). Lipin1 mRNA undergoes alternative splicing creating two isoforms, lipin1α and lipin1β. Lipin1β is a longer form containing an insertion of 33 amino acids (31.Peterfy M. Phan J. Reue K. J. Biol. Chem. 2005; 280: 32883-32889Abstract Full Text Full Text PDF PubMed Scopus (174) Google Scholar). During the maturation of adipocytes, the increase of lipin1α (the shorter isoform of lipin1) is less than that of lipin1β (Fig. 1A). As previously reported (10.Christy R.J. Kaestner K.H. Geiman D.E. Lane M.D. Proc. Natl. Acad. Sci. U. S. A. 1991; 88: 2593-2597Crossref PubMed Scopus (329) Google Scholar, 11.Clarke S.L. Robinson C.E. Gimble J.M. Biochem. Biophys. Res. Commun. 1997; 240: 99-103Crossref PubMed Scopus (187) Google Scholar, 12.Ramji D.P. Foka P. Biochem. J. 2002; 365: 561-575Crossref PubMed Google Scholar, 13.Farmer S.R. Cell Metab. 2006; 4: 263-273Abstract Full Text Full Text PDF PubMed Scopus (1364) Google Scholar), expression of both C/EBPα and PPARγ2 showed a gradual increase during the maturation of 3T3-L1 cells (14.Seo J.B. Moon H.M. Kim W.S. Lee Y.S. Jeong H.W. Yoo E.J. Ham J. Kang H. Park M.G. Steffensen K.R. Stulnig T.M. Gustafsson J.A. Park S.D. Kim J.B. Mol. Cell. Biol. 2004; 24: 3430-3444Crossref PubMed Scopus (206) Google Scholar, 32.Rosen E.D. Ann. N. Y. Acad. Sci. 2002; 979 (and 188-196): 143-158Crossref PubMed Scopus (64) Google Scholar), similar to lipin1 (Fig. 1A). C/EBPα and PPARγ2 are known to induce adipocyte-specific genes such as phosphoenolpyruvate carboxykinase (PEPCK) and adipocyte/macrophage fatty acid-binding protein (aP2) (13.Farmer S.R. Cell Metab. 2006; 4: 263-273Abstract Full Text Full Text PDF PubMed Scopus (1364) Google Scholar, 33.Bogacka I. Xie H. Bray G.A. Smith S.R. Diabetes Care. 2004; 27: 1660-1667Crossref PubMed Scopus (177) Google Scholar, 34.Duplus E. Benelli C. Reis A.F. Fouque F. Velho G. Forest C. Biochimie (Paris). 2003; 85: 1257-1264Crossref PubMed Scopus (22) Google Scholar). Additionally, the expression pattern of PEPCK and aP2 was similar to that of C/EBPα, PPARγ2, and lipin1 (Fig. 1A). Consistent with their involvement in adipocyte maturation (14.Seo J.B. Moon H.M. Kim W.S. Lee Y.S. Jeong H.W. Yoo E.J. Ham J. Kang H. Park M.G. Steffensen K.R. Stulnig T.M. Gustafsson J.A. Park S.D. Kim J.B. Mol. Cell. Biol. 2004; 24: 3430-3444Crossref PubMed Scopus (206) Google Scholar), the expression of LXRα and SREBP-1c expression also persisted through the maturation of 3T3-L1 cells (Fig. 1A). The levels of lipin1 protein strictly coincide with those of its mRNA, increasing 2 days after the onset of hormonal stimulation and reaching high levels in mature adipocytes (Fig. 1B). The protein levels of C/EBPβ, C/EBPα, and PPARγ2 also match with those of their mRNA. Taken together, these findings indicate that lipin1 was induced at a late stage and maintained at a high level in mature adipocytes in a pattern that was similar to the late adipogenic factors C/EBPα and PPARγ2 rather than the early adipogenic factor, C/EBPβ. Lipin1 Is Necessary for 3T3-L1 Adipocyte Differentiation—The pattern of lipin1 expression in 3T3-L1 cells suggests that lipin1 is involved in adipocy